History of Endoscopic Spine Surgery in India - Bajaj, Jitin; Yadav, Yad Ram (Indian Journal of Neurosurgery, 2022)
Endoscopic spine surgeries provide distinct advantages and is therefore a viable alternative to open or microscopic techniques. Indian surgeons have shown their expertise from craniovertebral junction to lumbosacral spine with these techniques. Many novel approaches like endoscopic transcervical, partial corpectomy, and others have been designed, and many technological innovations for these surgeries have been made. With different training programs attracting both native and international surgeons, the future of endoscopic spine surgery is bright.
Keywords: Minimally invasive surgical procedures; Neuroendoscopy; Spinal cord